IMPLEMENTASI PENCEGAHAN ‎PORNOGRAFI DALAM AL-QUR’AN (STUDI ‎PENAFSIRAN TERHADAP Q.S AN-NUR AYAT ‎‎30-31 MENURUT PROF. DR. HAMKA DALAM ‎TAFSIR AL AZHAR)‎ - Hidayatullah, Muhammad Hafiz (Jurnal Ushuluddin, 2024)
The development of technology and information has raised new issues for society. Among the problems that often occur and are difficult to prevent is pornography. Pornography does not recognize age limits; everyone can access it freely. The main factor that makes pornography difficult to prevent is the advancement of technology, which facilitates the dissemination of pornographic websites on social media. To address this issue, self-awareness is needed to prevent pornography, such as engaging in beneficial activities, avoiding spending time alone where others cannot see, and getting closer to Allah SWT by performing prayers, fasting, and reading the Qur'an. This study, titled "Implementation of Pornography Prevention in the Qur'an (Interpretation Study of Q.S An-Nur Verses 30-31 According to Prof. Dr. Hamka in Tafsir Al-Azhar)," serves as a scientific work to explore the prevention of pornography in the Qur'an using the tahlili method with an adabi ijtima’i interpretative approach. In this study, the author presents an interpretation of the Qur'an discussing efforts to prevent pornography, and analyzes the interpretation of Surah An-Nur verses 30-31 in Tafsir Al-Azhar. The results of this study reveal how the Qur'an provides solutions or preventive measures against pornography, such as restraining the gaze from things that may arouse sexual desires, preserving chastity from immoral acts like masturbation, adultery, homosexuality, and lesbianism, as well as covering the private parts.Keywords: Pornografi, QS. An-Nur: 30-31. Tafsir Al-Azhar, Hamka